How do volatile and non-volatile energy factors affect energy OFDI? evidence from simultaneous equation model - Liu, Yanfeng; Jin, Mengjie; Zhao, Shanshan; Qi, Guanqiu (Frontiers in Energy Research, 2024)
Its reliance on energy from individual countries has seriously affected its energy security and foreign policy. Therefore, reducing dependence on energy from specific countries and decomposing energy import channels have become crucial goals in China’s efforts to resolve its energy crisis and ensure its national energy security. This study aims to analyze the impact of energy factors on the location determinants of China’s energy OFDI to help reduce energy dependence and improve China’s energy security. Simultaneous equation models and panel data from 162 target countries for the period 2005–2020 are used to examine the coincidental relationship between volatile and non-volatile energy and intermediary factors in investment target countries and China’s energy OFDI. The simultaneous equation model, comprising a system of equations, constitutes a multifaceted modeling approach that allows examination of two or more dependent variables. This study provides insights into energy investment in China through simultaneous equation modelling, it guides the implementation strategies for home and target countries of energy investment.